Strife in the rural idyll? The relationship between autochthons and in-migrants in scenic regions of South Bavaria - Dirksmeier, Peter (ERDKUNDE, 2008)
The notion of the rural idyll as a conception of a healthy life in a natural environment goes back to the eclogues of Theocritus and Virgil. Since the 1970s this idea has gained greater attention in the anglophone human-geographical literature. Representations of the idyll are regarded as a crucial motive for the influx of urban middle classes into exurban, scenic rural regions. This in-migration gives rise to conflicts between the autochthonous inhabitants and the in-migrants, however. Disputes arise over changing real estate prices and changing social values as well as diverging opinions on the need for countryside protection. These controversies have been examined by anglophone geographical researchers particularly from the perspective of the new inhabitants. On the basis of two examples in South Bavaria, namely the municipalities of Tegernsee and Bodolz/Lake Constance, this essay focuses on the point of view of the autochthonous population concerning the implications of the influx motivated by idyllic notions. The article thus offers a contrast to the anglophone empirical studies. A major finding of the essay is that conflicts in Southern Bavaria can be attributed to changes induced by the real estate market only.